Predicted relative prevalence estimates for obstructive sleep apnoea and the associated healthcare provision across the UK. Issue 4 (23rd September 2013) - Steier, Joerg; Martin, Alistair; Harris, Judy; Jarrold, Ian; Pugh, Darien; Williams, Adrian
Abstract : We surveyed the UK distribution of five factors commonly associated with obstructive sleep apnoea (OSA) to produce an overall risk map that could be used to predict relative prevalence estimates. The weighting and mapping of selected risk factors associated with OSA highlighted significant regional variation in predicted prevalence estimates. These data provide the first attempt to systematically map the UK for OSA and identify areas where the condition is likely to be more prevalent. The data show a significant mismatch between areas identified as having a high predicted prevalence estimate and the distribution of existing sleep centres.